Distinguishing Between Biological and Technical Replicates in Hypertension Research on Isolated Arteries - Tsvetkov, Dmitry; Kolpakov, Evgeniy; Kassmann, Mario; Schubert, Rudolf; Gollasch, Maik (Frontiers in Medicine, 2019)
Perivascular adipose tissue (PVAT) is implicated in the pathophysiology of cardiovascular disease, especially in obese individuals in which the quantity of renal and visceral PVAT is markedly increased. The control of arterial tone by PVAT has emerged as a relatively new field of experimental hypertension research. The discovery of this prototype of vasoregulation has been mostly inferred from data obtained using wire myography. Currently, there is a major discussion on distinguishing between biological vs. technical replicates in biomedical studies, which resulted in numerous guidelines being published on planning studies and publishing data by societies, journals and associations. Experimental study designs are determined depending on how the experimentator distinguishes between biological vs. technical replicates. These definitions determine the ultimate standards required for making submissions to certain journals. In this article, we examine possible outcomes of different experimental study designs on PVAT control of arterial tone using isolated arteries. Based on experimental data, we determine the sample size and power of statistical analyses for such experiments. We discuss whether n-values should correspond to the number of arterial rings and analyze the resulting effects if those numbers are averaged to provide a single N-value per animal, or whether the hierarchical statistical method represents an alternative for analyzing such kind of data. Our analyses show that that the data (logEC50) from (+) PVAT and (–) PVAT arteries are clustered. Intraclass correlation (ICC) was 31.4%. Moreover, it appeared that the hierarchical approach was better than regular statistical tests as the analyses revealed by a better goodness of fit (v2-2LL test). Based on our results, we propose to use at least three independent arterial rings from each from three animals or at least seven arterial rings from each from two animals for each group, i.e. (+) PVAT vs. (–) PVAT. Finally, we discuss a clinical situation where distinguishing between biological vs. technical replicates can lead to absurd situations in clinical decision makings. We conclude that discrimination between biological vs. technical replicates is helpful in experimental studies but is difficult to implement in everyday’s clinical practice.